Framing Taxes as Losses: A Phenomenological Study of Mental Accounting and Compliance Behaviour in Indonesia - Aziz, Muhammad Abdil; Fidiana, Fidiana (Nauki o Finansach, 2025)
Aim: This study examined how taxpayers perceive and manage their tax liabilities through an accounting mental approach. Methodology: Employing a phenomenological approach, the authors conducted in-depth interviews with tax consultants and clients experienced in fulfilling tax obligations. Data were analysed through bracketing, categorisation, and thematic development. Findings: Five themes emerged: tax and corruption as intertwined tensions, consultants as facilitators of legal avoidance, bookkeeping as a strategic tool, low-risk avoidance as a preferred option, and compliance as a subtle psychological struggle. Taxpayers commonly frame taxes as entries in a ‘loss account’, prompting loss-aversion strategies to minimise liabilities whilst remaining lawful. Consultants act as both technical experts and psychological intermediaries who translate taxpayers’ fear of sanctions into avoidance strategies. Implications: The study extends the ‘slippery slope’ theory by showing how loss framing shapes compliance in Indonesia, and underlines the dual role of tax consultants, highlighting the need of policy to rebuild trust and reframe taxation as a civic responsibility to encourage voluntary compliance. Originality/value: By revealing how negative tax framing and distrust interact to shape compliance, the study offers new insights into tax behaviour in contexts where legality, avoidance, and low institutional trust converge.
Financial Sciences. Nauki o Finansach, 2025, vol. 30, no. 2, s. 14-22
Keywords: tax compliance; phenomenology; loss aversion; legal avoidance; tax consultants; slippery slope theory